2021
DOI: 10.4046/trd.2020.0021
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Inhaler Use Technique Based on Inhaler Type in Elderly Patients with Respiratory Disease

Abstract: Background We aimed to investigate inhaler device handling in elderly patients. Furthermore, we compared inhaler devices with respect to misuse and error correction. Methods Inhaler use technique was assessed using standardized checklists at the first and 3-months follow-up visits after retraining. The primary outcome was differences in the acceptable use ratio among inhaler devices. Secondary outcomes included differences in error correction, most common step of misuse, and factors affecting the accuracy of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…However, inhaler handling errors and suboptimal adherence are common, and are associated with adverse clinical outcomes such as acute exacerbations. 1 2 Low inhaler satisfaction is an important risk factor for inhaler handling errors and suboptimal adherence in COPD patients. 3 4 The Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines also recommend that patient preference be considered when choosing an inhaler device.…”
Section: Introductionmentioning
confidence: 99%
“…However, inhaler handling errors and suboptimal adherence are common, and are associated with adverse clinical outcomes such as acute exacerbations. 1 2 Low inhaler satisfaction is an important risk factor for inhaler handling errors and suboptimal adherence in COPD patients. 3 4 The Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines also recommend that patient preference be considered when choosing an inhaler device.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported a negative correlation between the CAT score (OR 0.960, 95% CI 0.927-0.994) and the acceptable use of inhalers in elderly patients with respiratory disease. 6 In other studies, a lower CAT score was associated with high physician-and patient-reported confidence in inhaler usage, 20 and a shortterm comprehensive education program that included inhaler training and disease management for COPD patients improved the CAT score (19.6±12.5 vs 15.1±12.3, P < 0.05). 21 Our study provides further evidence of the relationship between disease control as assessed by the CAT and inhaler technique in groups using pMDI-type inhalers.…”
mentioning
confidence: 80%
“…5 However, few studies have compared inhaler device handling technique and the risk factors for critical inhaler errors in the Asian COPD population. 6,7 Thus, in this study we evaluated the rates and risk factors for any critical inhaler error in the COPD population in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…4 Many patients, particularly children and elderly people, may also have difficulty with the dexterity and coordination required. 5 Sufficient dexterity is needed to handle, load, shake, and prime the inhaler, whereas ample coordination is required to synchronize inhalation with the operation of the device (if not breathactuated and particularly if a spacer device is not used with a pMDI), ensuring fluidity of the inhalation maneuver.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested that although even a single education session can significantly improve inhalation technique, 9 at least three rounds of education are likely required to eliminate all errors for a sustained period, 10 and that repeated training has a greater clinical impact on disease control than the precise type of inhaler used. 5 Given these facts, it is unsurprising that poor inhaler technique has health economic and societal implications. 1,11 Inhaler following relevant financial activities to declare: P.N.R.…”
Section: Introductionmentioning
confidence: 99%